LINC01559 drives osimertinib resistance in NSCLC through a ceRNA network regulating miR-320a/IGF2BP3 axis - Xu, Leidi; Zhang, Yibo; Xing, Liangliang; Zhou, Ying; Chang, Ning; Xi, Hangtian; Xu, Xiangrui; Zhang, Jian (Frontiers in Pharmacology, 2025)
BackgroundOsimertinib resistance remains a major challenge in the treatment of lung adenocarcinoma. Long non-coding RNAs (lncRNAs) have emerged as key regulators of drug resistance, but their roles in osimertinib resistance are poorly understood. This study aimed to identify lncRNAs driving osimertinib resistance and elucidate their molecular mechanisms.MethodsMulti-cohort analysis (GSE222820, GSE232890, GSE255958) identified osimertinib resistance-associated lncRNAs. Functional validation employed in vitro assays (proliferation, migration, invasion, drug sensitivity) and xenograft models. Mechanistic studies involved luciferase reporter assays, RNA immunoprecipitation (RIP), and Western blotting. Clinical correlations were analyzed using TCGA-LUAD data.ResultsOur findings demonstrated that LINC01559 was markedly upregulated in LUAD tissues and osimertinib-resistant cell lines, correlating with poor patient survival. Functional analyses revealed that LINC01559 critically regulates processes linked to drug resistance, enhancing tumor cell proliferation, migration, and invasive capabilities. Knockdown of LINC01559 sensitized resistant cells to osimertinib, significantly reducing colony-forming potential and suppressing migratory/invasive behaviors. In contrast, overexpression of LINC01559 exacerbated therapeutic resistance. Mechanistically, LINC01559 functions as a competing endogenous RNA (ceRNA) by sponging miR-320a, promote osimertinib -resistance and upregulate the expression of the miR-320a target IGF2BP3. Rescue experiments and xenograft models confirmed that Linc01559 drives resistance via the miR-320a/IGF2BP3 axis.ConclusionThis study identifies LINC01559 as a novel ceRNA that drives osimertinib resistance in lung adenocarcinoma by sponging miR-320a to enhance IGF2BP3 expression. Targeting the LINC01559/miR-320a/IGF2BP3 axis may provide a therapeutic strategy to overcome osimertinib resistance.